Current Research of Traditional Chinese Medicine and Western Medicine on Chronic Pelvic Pain Caused by Gynecological Pelvic Tumors - Zhou, Kainan; Zhang, Ying (Zhongliu fangzhi yanjiu, 2021)
Chronic pelvic pain with pelvis pain as its main manifestation often occurs in the process of the occurrence, development and treatment of gynecologic pelvic tumors which mainly include ovarian cancer, cervical cancer and endometrial cancer. It seriously affects the physical health, mental health and quality of life of female pelvic cancer patients. At present, there are few relevant studies on chronic pelvic pain caused by gynecological pelvic tumors and lack of research on TCM syndromes. There is no targeted diagnosis and therapy until now. This paper discusses the related concepts of chronic pelvic pain, the characteristics of chronic pelvic pain caused by different pelvic tumors and the current status of diagnosis and therapy of chronic pelvic pain, to provide a reference for further research on the symptoms and clinical diagnosis and treatment of chronic pelvic pain caused by gynecological pelvic tumor.